2014
DOI: 10.1371/journal.pone.0112413
|View full text |Cite
|
Sign up to set email alerts
|

Higher Vulnerability and Stress Sensitivity of Neuronal Precursor Cells Carrying an Alpha-Synuclein Gene Triplication

Abstract: Parkinson disease (PD) is a multi-factorial neurodegenerative disorder with loss of dopaminergic neurons in the substantia nigra and characteristic intracellular inclusions, called Lewy bodies. Genetic predisposition, such as point mutations and copy number variants of the SNCA gene locus can cause very similar PD-like neurodegeneration. The impact of altered α-synuclein protein expression on integrity and developmental potential of neuronal stem cells is largely unexplored, but may have wide ranging implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 65 publications
2
90
0
1
Order By: Relevance
“…7C) and mRNA quantitation by RT-PCR (Fig. 7D), consistent with previous studies [51]. DNA damage analysis by LAPCR showed presence of significantly higher number of DNA strand breaks in SNCA-tri NPC cells compared to control NPC cells (Fig.…”
Section: Resultssupporting
confidence: 90%
“…7C) and mRNA quantitation by RT-PCR (Fig. 7D), consistent with previous studies [51]. DNA damage analysis by LAPCR showed presence of significantly higher number of DNA strand breaks in SNCA-tri NPC cells compared to control NPC cells (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Increased levels of wild-type α-synuclein cause mitochondrial impairment and an increase in superoxide and other reactive oxygen species (28, 29), possibly because of interference with mitochondrial protein import (30). We tested whether clenbuterol may be helpful in normalizing SNCA expression levels in human iPSC derived neuronal cells of a patient carrying the SNCA triplication.…”
Section: β2ar Agonist In Patient-derived Cells Carrying a Snca Triplimentioning
confidence: 99%
“…Furthermore, PD patient–derived neuronal precursor cells carrying the pathogenic SNCA locus triplication show increased mitochondria associated superoxide production and reduced viability under exposure to the environmental mitochondrial complex I toxin rotenone (28). Clenbuterol treatment ameliorated this increased mitochondria-associated superoxide production (Fig.…”
Section: β2ar Agonist In Patient-derived Cells Carrying a Snca Triplimentioning
confidence: 99%
“…3c). Indeed, increased cellular stress and ROS levels have been observed in stem cell-derived neuronal precursor cells of a PD patient carrying a SNCA triplication (Flierl et al 2014). Pukaß and colleagues showed that the application of mitochondrial stressors induced a decrease of autophagic clearance of alpha-synuclein, which causes alpha-synuclein accumulation (Pukaß et al 2015).…”
Section: Genetic Risk Factors Linked To Impaired Mitochondrial Functimentioning
confidence: 99%